2000
DOI: 10.1073/pnas.040378897
|View full text |Cite
|
Sign up to set email alerts
|

Pw1/Peg3 is a potential cell death mediator and cooperates with Siah1a in p53-mediated apoptosis

Abstract: Induction of wild-type p53 in mouse fibroblasts causes cell cycle arrest at the G1 phase, whereas coexpression of p53 and the protooncogene c-myc induces apoptosis. Although p53 transcriptional activity generally is required for both pathways, the molecular components mediating p53-dependent apoptosis are not well understood. To identify factors that could mediate p53-induced cell death, we used a comparative RNA differential display procedure. We have identified Pw1͞Peg3 as a gene product induced during p53͞c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
161
2
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(174 citation statements)
references
References 23 publications
8
161
2
3
Order By: Relevance
“…RNA expression peaked at 7 h post-treatment and decreased later on ( Figure 6a, and not shown). In addition, the BH3-protein PUMA, 17,18 the zinc finger protein Peg3, 69 and the p53 target gene p21/WAF1 70 were induced in a p53-dependent manner (Figure 6a). In contrast, the expression of proapoptotic Bak, which acts at the same level as Bax during stressinduced apoptosis in MEF, 71,72 remained unchanged following etoposide treatment (Figure 6a).…”
Section: Resultsmentioning
confidence: 98%
“…RNA expression peaked at 7 h post-treatment and decreased later on ( Figure 6a, and not shown). In addition, the BH3-protein PUMA, 17,18 the zinc finger protein Peg3, 69 and the p53 target gene p21/WAF1 70 were induced in a p53-dependent manner (Figure 6a). In contrast, the expression of proapoptotic Bak, which acts at the same level as Bax during stressinduced apoptosis in MEF, 71,72 remained unchanged following etoposide treatment (Figure 6a).…”
Section: Resultsmentioning
confidence: 98%
“…The murine Siah-1b was reported to be a direct transcriptional target of p53 (Fiucci et al, 2004). Some studies have also suggested that human Siah-1 may act as a downstream effector of p53 (Hu et al, 1997a;Matsuzawa et al, 1998;Roperch et al, 1999;Relaix et al, 2000;Liu et al, 2001;Maeda et al, 2002). However, the mechanism by which p53 induces human Siah-1 gene is still unclear.…”
mentioning
confidence: 92%
“…This suggested a deficit in the neurobiological control of lactation, and investigations demonstrated a reduced number of oxytocin-positive neurons in the hypothalamus of Peg3 mutant females (Li et al 1999). Given the central role played by oxytocin in both maternal behaviour and milk letdown, the indication is that this is the neurobiological pathway via which Peg3 is exerting an effect (Keverne 2001), an idea that sits nicely with its involvement in the tumour necrosis factor signalling pathway affecting NFkB phosphorylation, apoptosis and cell survival (Relaix et al 1998(Relaix et al , 2000.…”
Section: The Pre-weaning Period and Mother-offspring Bondingmentioning
confidence: 99%